Morfonologinės balsių kaitos funkcijos - Akelaitienė, Gražina (Baltistica, 1997)
THE FUNCTIONS OF MORPHONOLOGICAL VOWEL CHANGE The article deals with morphonological interpretation of vowel change. Non-automatic vowel change makes contrast between the motivated word (marked member) and simple word (unmarked member) more expresive. Changes in the stem of basic word performs an informative function: šūk- + -is, bar- + -stīti, pastab- + -a. There are some oppositions in which the function of vowel change becomes close to an internal flexion: laužti ‘to break smth’ : lūžti ‘to break up (spontaneously)’. In the Lithuanian language there are such word-formation oppositions in which semiosis can be recognized (a parallel between the content and expression): snigti ‘to snow’ : sneigėti ‘to snow quietly’. That, vowel change can perform not only informative, but also an iconic function